EKSISTENSI BANK TANAH DALAM HUKUM AGRARIA DI INDONESIA - Nila Trisna; Ilka Sandela (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Development in Indonesia is increasing day by day, it’s resulting in an increasing need for land. However, the limited availability of land will hamper the development process. Based on these conditions, a solution is needed that can guarantee the availability of land. In Law Number 11 of 2020 concerning Job Creation provides a solution related to this, namely the formation of a land bank to ensure the availability of land that can be allocated for future use. This study aims to examine the philosophical and juridical foundations for the establishment of land bank institutions and the regulation of land banks according to Law Number 11 of 2020 concerning Job Creation, and the concept of implementing land bank institutions in Indonesia. The research method used is a normative juridical research method. The results show that the philosophical and juridical foundation for the establishment of a land bank is that the state has the state's obligation to create welfare and prosperity for all Indonesian people as stated in the opening mandate and Article 33 of the 1945 Constitution of the Republic of Indonesia. As for the regulation of land banks according to Law Number 11 of 2020 concerning Job Creation, which is contained in Chapter VIII concerning Land Acquisition, Part Four concerning Land in accordance with Articles 125-135. Then, the concept of implementing a land bank in Indonesia can be implemented through the land acquisition mechanism of existing community rights and government designation for state lands. In addition, land banks are not only for the development of public interests that are for profit, but also for the purpose of supporting non-profit Social Interest and agrarian reform programs.